2022
DOI: 10.1002/jsc.2488
|View full text |Cite
|
Sign up to set email alerts
|

A case of trust‐building in the supply chain: Emerging economies perspective

Abstract: The paper explores the process of trust‐building between SMEs' supply chain partners in turbulent times in emerging economies. It focuses on the role of environmental information exchange in strengthening relationships and improving responsiveness to overcome uncertainty while understanding and adapting to the changing environmental realities. A case study strategy of an SME in Argentina was conducted to obtain insights regarding the experiences, perceptions and opinions about how achieving trust acts as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 69 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…A characteristic of this scenario is that trust develops over time, requires consistency, and significantly predicts chain actors' supply chain governance choices, agreeing with Aggarwal and Srivastava (2016), Manfredini and Capik (2022), Love et al. (2020), and Dlamini-Mazibuko et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A characteristic of this scenario is that trust develops over time, requires consistency, and significantly predicts chain actors' supply chain governance choices, agreeing with Aggarwal and Srivastava (2016), Manfredini and Capik (2022), Love et al. (2020), and Dlamini-Mazibuko et al.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Ervasti et al (2019), for example, shows that when analysing the levels of trust in Greece in the period from 2002 to 2011, during a severe socio-economic crisis, interpersonal trust increased, to the surprise of the authors. Along the same line, Manfredi and Capik (2022) concluded that trust is built in response to the uncertainty of a business environment.…”
Section: Trust For Sustainable Agri-food Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interpersonal trust acknowledges individual interdependence while relying on conduct. However, expectations are more important to interorganizational trust than commitments and agreements made in commercial dealings with the intention of lowering risk [34]. Numerous elements influence trust, including the competence, skill, and reputation of trustees, and the emotions, experience, and cognition of trustors [35].…”
Section: Conceptualization Of Trustmentioning
confidence: 99%
“…Nowadays, to keep competitiveness levels high, SCs need to be flexible to respond rapidly to changes in the business and social environments, and collaboration requirements remain challenging to some networks [42]. One of the greatest difficulties for SCs is trust.…”
Section: Current Challenges In Supply Chain Managementmentioning
confidence: 99%